2022
DOI: 10.3390/bios12020062
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic µPAD for Purification and Analysis of DNA Samples

Abstract: In this work, the fabrication and characterization of a simple, inexpensive, and effective microfluidic paper analytic device (µPAD) for monitoring DNA samples is reported. The glass microfiber-based chip has been fabricated by a new wax-based transfer-printing technique and an electrode printing process. It is capable of moving DNA effectively in a time-dependent fashion. The nucleic acid sample is not damaged by this process and is accumulated in front of the anode, but not directly on the electrode. Thus, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(58 reference statements)
0
3
0
1
Order By: Relevance
“…In a recent study, the dominance of Bradyrhizobium bacteria in tropical soils when diagnosed with the 16S rRNA gene, the study also suggested that the variable regions in this gene located between V5-V7 may be a suitable indicator to distinguish between the noduleforming bacteria in the genus level [9].…”
Section: Introductionmentioning
confidence: 94%
“…In a recent study, the dominance of Bradyrhizobium bacteria in tropical soils when diagnosed with the 16S rRNA gene, the study also suggested that the variable regions in this gene located between V5-V7 may be a suitable indicator to distinguish between the noduleforming bacteria in the genus level [9].…”
Section: Introductionmentioning
confidence: 94%
“…The amplified DNA samples have different sizes of fragmentation present that need to be examined thoroughly, and the electrophoresis helps in understanding this process (Heinsohn et al 2022). In this process, 50x TAE (Tris-acetate-EDTA) buffer, distilled water, ethidium bromide, and agarose powder were used as the main ingredients to prepare the agarose gel bed to study the amplified bacterial DNA samples.…”
Section: Electrophoresismentioning
confidence: 99%
“…The paper CE chip can effectively isolate long dsRNA at concentrations close to those found in infected cells, offering a new platform for ultrafast viral disease detection at the POCT level. Additionally, Heinsohn et al [ 214 ] utilized glass fiber paper as a sieving matrix in an economical and effective portable microfluidic device for DNA monitoring. The device efficiently transports nucleic acid without causing damage and facilitates additional DNA processing and purification.…”
Section: Detection Techniquesmentioning
confidence: 99%